2016
DOI: 10.3892/ijmm.2016.2546
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog-mediated epithelial-mesenchymal transition in renal tubulointerstitial fibrosis

Abstract: Abstract. The sonic hedgehog (SHH) signaling pathway plays a critical role in embryonic development, tissue regeneration and organogenesis. The activation of SHH signaling produces profibrogenic effects in various tissues, such as the liver and the biliary ducts. However, the role of SHH signaling in renal fibrogenesis remains to be elucidated. For this purpose, in the present study, we evaluated the hypothesis that activated SHH signaling promotes the acquisition of a myofibroblastic phenotype through the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…It has been shown that hypermethylation of Ptch1 is associated with the perpetuation of broblast activation and brosis in the liver [30] . Similarly, inhibition of Ptch1 may have pro-brotic effects in kidney tissue by activating Hh signaling [31,32]. Furthermore, Ptch1 gene mutations have been suggested to play an essential role in the pathogenesis of nephroblastoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hypermethylation of Ptch1 is associated with the perpetuation of broblast activation and brosis in the liver [30] . Similarly, inhibition of Ptch1 may have pro-brotic effects in kidney tissue by activating Hh signaling [31,32]. Furthermore, Ptch1 gene mutations have been suggested to play an essential role in the pathogenesis of nephroblastoma [33].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the mesothelial cells produce TGF-β1, a key cytokine for EMT, progressively lose their epithelial characteristics and convert to a mesenchymal phenotype [21]. The cells attain mesenchymal characteristics, which include enhanced migratory capacity and increased extracellular matrix (ECM) production [5,8]. Previous studies found that ECM deposition plays an important role in the development of peritoneal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interest in SHH signaling has expanded to its role in tissue fibrosis. Bai et al [8] reported that activation of the SHH signaling pathway promotes the EMT process and renal tubulointerstitial fibrosis. Ding et al [9] also demonstrated that SHH signaling plays a pivotal role in fibroblast activation and development of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations